Kapang pada tingkat kematangan gambut yang berbeda di kawasan Hutan Lindung Gunung Ambawang Kabupaten Kubu Raya - Siti Khotimah, Efa Rosita, Riza Linda, (Jurnal Protobiont, 2014)
Peat is formed from organic materials derived from the remains of dead plants and accumulated over thousands of years. Dead plants will undergo decomposition quickly by molds and bacteria. This research aims to identify the genus of molds at different levels of maturity of peat in the area of the Protected Gunung Ambawang Forest in Kubu Raya District. Peat sampling used the stratified random sampling method based on the degree of maturity of the peat soil i.e. fibric peat, hemic peat, and sapric peat. The isolation of molds employed the method of dilution plate with dilution 10-3 at the medium of PDA (Potato Dextrose Agar) and CYA (Czapeck Yeast Agar). The result of research on fibric peat showed that six pure isolates of mold were found i.e. Aspergillus niger, Fusarium sp.1, Paecilomyces sp.2, Penicillium variabile, Phialophora sp., and Verticillium sp. On hemic peat 10 pure isolates were found: A. niger, Fusarium sp.2, Mortierella sp., Paecilomyces sp.1, Paecilomyces sp.3, Penicillium sp.3, Penicillium sp.4, Penicillium sp.5, Rhizopus sp., and T. harzianum. On sapric peat 12 pure isolates were found: Fusarium sp.3, Paecilomyces sp.1, Paecilomyces sp.4, Penicillium sp.1, Penicillium sp.2, Penicillium sp.3, Penicillium sp.6, Penicillium sp.7, Penicillium sp.8, Penicillium sp.9, Pythium sp., and Trichoderma sp.